2013
DOI: 10.1111/lam.12129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of purple nonsulfur bacteria grown under Stevia residue extractions

Abstract: Significance and Impact of the Study: This study first reported that the purple nonsulfur bacteria could grow well and possess high quality using Stevia residue extractions as carbon source. Those results suggest that wastewater of Stevia residue can be a favourable substrate for microbial growth, which can further provide desired bioresources for the application of downstream industry. AbstractAs a consequence of the large-scale cultivation of Stevia plants, releases of plant residues, the byproduct after sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Particularly, R. palustris grown under Stevia residue extract showed more remarkable influence, which might be attributed to the individual characteristics of R. palustris. As shown in our preceding report, R. palustris grown under Stevia residue extract has higher cytochrome content in live cells as compared to that grown under the chemical medium (Xu et al 2013a). Besides, our unpublished data showed that the ability of excreting 5-aminolevulinic acid (5-ALA) was also high in the R. palustris grown under Stevia residue extract.…”
Section: Promotion Effects Of R Palustris On Plant Growthmentioning
confidence: 84%
See 3 more Smart Citations
“…Particularly, R. palustris grown under Stevia residue extract showed more remarkable influence, which might be attributed to the individual characteristics of R. palustris. As shown in our preceding report, R. palustris grown under Stevia residue extract has higher cytochrome content in live cells as compared to that grown under the chemical medium (Xu et al 2013a). Besides, our unpublished data showed that the ability of excreting 5-aminolevulinic acid (5-ALA) was also high in the R. palustris grown under Stevia residue extract.…”
Section: Promotion Effects Of R Palustris On Plant Growthmentioning
confidence: 84%
“…The NH 4 Cl is a common N source, while L-tryptophan is the precursor of indole-3-acetic acid (IAA), a typical phytohormone regulating various developmental and physiological processes in plants ( Kim et al 2004). Our preceding report has shown that R. palustris exhibits distinct growth pattern and genotypic characteristics under such N sources (Xu et al 2013a). Yet, whether those changes would influence the downstream application of R. palustris is still unknown so far.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The cost is primarily due to expensive nitrogen sources, such as yeast extract and peptone. On the other hand, some media have low-cost sources; for example, Xu et al [31] used Stevia residue extractions supplied with NH 4 Cl as a medium to culture R. palustris, and the highest obtained biomass was 1.5 (OD 660 ) (approximately equivalent to 0.77 g/L) after 96 hours of cultivation. Kornochalert et al [9] obtained the 0.9 g/L R. palustris in latex rubber sheet wastewater supplied with pineapple extract after 96 hours of fermentation.…”
Section: Introductionmentioning
confidence: 99%